Comparison of High Intensity Laser and Epicondylitis Bandage in the Treatment of Lateral Epicondylitis - Ali SALLI,; Ekrem AKKURT,; Alparslan Ali İZKİ,; Zafer ŞEN,; Halim YILMAZ, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the effects of high-intensity laser therapy (HILT) and epicondylitis bandage treatment in patients with lateral epicondylitis (LE). Patients and methods: Sixty-five patients with unilateral LE (18 males, 47 females; mean age 46.5±8.1 years; range 30 to 61 years) with unilateral complaints were included. Patients were randomly assigned into two treatment groups. The first group (n=31) was treated with HILT for 10 sessions, while the second group (n=34) used only LE bandage for treatment. The patients were assessed for handgrip strength, pain, disability, and quality of life at baseline and sixth week after treatment by using visual analog scale, the Disabilities of the Arm Shoulder and Hand questionnaire, and Short-Form 36 (SF-36). Results: Both groups showed significant improvement in all evaluated parameters including pain scores, hand grip strength, disability, and SF-36 scores at sixth week after the treatment (all p<0.05). A comparison of percentage changes in parameters between treatment groups did not show a significant difference, except for resting visual analog scale (p=0.036) and SF-36 physical component subscale (p=0.049) scores which indicated better improvement in HILT group. Conclusion: Our findings showed significant improvement in handgrip strength, pain, disability, and quality of life parameters in both groups. However, HILT produced better resting visual analog scale and SF-36 physical component subscale scores compared to LE bandage.